PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA SLIDE TERHADAP PENGETAHUAN GENITAL HYGIENE SAAT MENSTRUASI PADA REMAJA PUTRI DI MAN 2 KOTA CIREBON - Ani Nurhaeni; Chintya Intansar; Sumarni (LPPM ITEKES Mahardika, 2018)
Adolescence is a very vulnerable time to reproductive health problems. One is about genital hygiene during menstruation. Information about genital hygiene during menstruation is very important for young women, with adolescent knowledge to prevent early infection of the reproductive organs. The right strategy to increase knowledge about genital hygiene during menstruation is to provide health education. The purpose of this study to determine the effect of health education using the slide media to the knowledge of genital hygiene during menstruation in adolescent girls in MAN 2 Kota Cirebon. This research is Quasi Eksperimental. The sample in this research are 42 students (experiment group) and 42 female students (control group), taken by using simple random sampling technique. The results showed that in the experimental group, there were 42 students (100%) had good knowledge while control group (not given intervention) there were 21 students (50%) had good knowledge. The conclusion of this research is health education using slide media can influence knowledge of genital hygiene during menstruation in adolescent girls with p-value = 0.000.